Relationship of Conflict Management on Employees’ Performance in a Private Sector Organisation in Nepal - Shrestha, Arbind; Singh, Balgopal (Journal of Economics and Management, 2024)
The purpose of this study is to investigate the ways in which approaches for resolving disagreements influence the performance of workers in private sector organisations. The following strategies for conflict resolution were taken into consideration: competing, avoiding, accommodating, compromising, and collaborating. With the descriptive survey design, the questionnaire that was prepared by the researcher was utilised. Both the Employee Performance Questionnaire and the Conflict Management Strategies that were tagged were utilised in the process of data collecting. According to the findings of the studies, techniques for conflict management have a major influence on the performance of employees. As a result, it was recommended that, in order to enhance the productivity of workers at their place of employment, disagreements of any kind should be skillfully managed rather than ignored. Individuals working at all levels of the organisation should be provided with the right behavioural guidance and training on how to handle conflict. Supervisors are required to get continual training on how to settle disagreements in order to bring about an increase in the productivity of workers while they are on the job.